Defini, Obyek, dan Tujuan Ilmu Semantik dengan Ilmu-Ilmu Lainnya - Liazy Maulidi (Al-Qalam: Jurnal Pendidikan Bahasa Arab, 2025)
Semantic science is a branch of linguistics that studies meanings in language, both lexical and grammatical meanings. As a discipline, semantics has an important role to play in understanding how language is used to convey messages, ideas, and emotions appropriately. This study aims to systematically describe the definitions, objects, and objectives of semantics and explain their relationship to other branches of linguistics, such as phonology, morphology, syntax, and pragmatics. The method used in this study is a qualitative method with a literature study approach, which is to collect data from various relevant literature to be analyzed descriptively. The results of the study show that semantics not only serves as a tool for understanding the meaning of words and sentences, but also becomes an important link between structural and functional aspects in language. Semantic relationships with other branches of linguistics are complementary in forming a comprehensive understanding of language as a system of human communication. Thus, understanding semantics is an important foundation in the development of language studies, both in the theoretical and practical realms.